PENGARUH PENGGUNAAN MEDIA KOMIK TERHADAP PENINGKATAN MINAT BELAJAR SISWA PADA MATA PELAJARAN PKn BAGI SISWA SD KELAS V - Zein Situmeang, Farid Zaki; Darwis, Umar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The research conducted aims to determine the effect of the use of comic media on increasing students' interest in learning PKn subjects for grade V elementary school students. This research is a quantitative approach using an experimental method. From the results of the research conducted, it is known that the use of comic media in PKn learning has a significant effect on the learning outcomes of grade V students of DN 060818 Medan. This can be seen from the t-count value of 3.498 and T_table 1.72. The Sig. (2-tailed) value <0.001, meaning <0.05. Because t_count> from t_table, H0 is rejected and Ha is accepted, which means that there is an effect of the use of comic media on increasing students' interest in learning in grade V of SDN 060818 Medan. The average difference between the two groups is 13.700 with a statistically significant difference, and the 95% confidence interval range is between 5.748 and 21.652. This shows that there is a significant difference between the two groups of classes being compared, namely the control and experimental classes.